2023
DOI: 10.1177/14780771231168232
|View full text |Cite
|
Sign up to set email alerts
|

Using deep learning to generate design spaces for architecture

Abstract: We present an early prototype of a design system that uses Deep Learning methodology—Conditional Variational Autoencoders (CVAE)—to arrive at custom design spaces that can be interactively explored using semantic labels. Our work is closely tied to principles of parametric design. We use parametric models to create the dataset needed to train the neural network, thus tackling the problem of lacking 3D datasets needed for deep learning. We propose that the CVAE functions as a parametric tool in itself: The solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…The final dataset is then more than a combination of all the parametric models' outputs as it also contains hybrids of those initial models. We have shown that a generative neural network is able to create a diverse solution-space that maps out all the parametric models but also their interpolation and combinations (Sebestyen et al, 2023). Furthermore, we showed that this new solution-space can be linked to descriptive keywords, which lets the user intuitively navigate it and thus generate novel geometries through semantic inputs.…”
Section: The Parametric Approachmentioning
confidence: 91%
See 1 more Smart Citation
“…The final dataset is then more than a combination of all the parametric models' outputs as it also contains hybrids of those initial models. We have shown that a generative neural network is able to create a diverse solution-space that maps out all the parametric models but also their interpolation and combinations (Sebestyen et al, 2023). Furthermore, we showed that this new solution-space can be linked to descriptive keywords, which lets the user intuitively navigate it and thus generate novel geometries through semantic inputs.…”
Section: The Parametric Approachmentioning
confidence: 91%
“…2019) which contradicts one of the main principles of deep learning, which is to acquire large datasets in order to achieve the most accurate results. In previous projects we have solved this problem by creating large datasets through parametric scripts (Sebestyen et al, 2023). This is achieved by randomizing parameters' inputs and thus creating a single output instance.…”
Section: The Parametric Approachmentioning
confidence: 99%